Deterioration of ancient metallic elements taken from Toledo cathedral (2001)
ABSTRACT: The construction of Toledo Cathedral spanned a period of more than 200 years and was influenced by many different trends and criteria, reflected in the wide range of styles it accoramodates (basically Mudejar and Gothic, with Fiemish, baroque and renaissance elements). Over the centuries it has undergone numerous restorations, also according to different criteria. The cathedral is situated in an environment of low aggressivity, in terms of atmospheric contamination, but the passage of time has taken its toll on many srructural, architectural and artistic elements. During recent restoration work several metallic elements, which have bcen exposed for many years or even centuries to the inclemencies of the Toledo climate, were taken in order to analyse their composition and deterioration. The techniques used have been Scanning Electron Microscopy with X-Ray Microprobe (SEM/EDAX), X-Ray Photoelectron Spectroscopy (XPS) and X-Ray Diffraction (XRD). The elements considered are a piece of roofing lead, a lead slate clamp, a piece of stamed glass window leading, and an iron nail